Risk Factors for Incident Dementia Among Older Cubans - Peeters, Geeske; Almirall Sanchez, Arianna; Llibre Guerra, Jorge; Lawlor, Brian; Kenny, Rose Anne; Yaffe, Kristine; Llibre Rodriguez, Juan (Frontiers in Public Health, 2020)
Introduction: Little is known about risk factors of dementia in Latin American countries. We aimed to identify socio-demographic, health and lifestyle risk factors of incident dementia in Cuban older adults. Methods: Data were from 1846 participants in the Cuban cohort of the 10/66 Dementia Research Group. Participants completed questionnaires, health examinations, and cognitive tests at baseline (2003-06) and 4.5 years later (2007-10). Associations between risk factors (baseline) and incident dementia (follow-up) were examined using logistic regression. Results: Just over 9% of participants developed dementia. Overall, older age and low physical activity were associated with incident dementia. In those 65-74 years of age, depression, stroke and low physical activity were associated with incident dementia. In those ≥75 years of age, low physical activity, never eating fish and smoking were associated with incident dementia. Conclusions: Modifiable lifestyle factors play an important role in developing dementia in Cuban older adults. This knowledge opens up opportunities for preventive strategies.